The first reported cases of Q fever endocarditis in Thailand - Orathai Pachirat; Pierre-Edouard Fournier; Burapha Pussadhamma; Suthep Taksinachanekij; Viraphong Lulitanond; Henry C. Baggett; Somsak Thamthitiwat; George Watt; Didier Raoult; Susan A. Maloney (MDPI AG, 2012)
We describe the first two reported cases of Q fever endocarditis in Thailand. Both patients were male, had pre-existing heart valve damage and had contact with cattle. Heightened awareness of Q fever could improve diagnosis and case management and stimulate efforts to identify risk factors and preventive measures.